1978
DOI: 10.1007/bf00537615
|View full text |Cite
|
Sign up to set email alerts
|

Stacking interaction of nucleobases: NMR investigations

Abstract: The stacking interaction between nucleic acid bases has been investigated by the determination of the self-association of 6-methylpurine in various mixtures of water and nonaqueous solvents in order to elucidate the solvent effect. The parameters of stacking association as well as of local solvent-solute interactions have been measured by means of NMR technique. The influences of local hydration and of solvent-solvent interactions on the stacking ability are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…However, for characterizing the transition states and the reaction intermediates, the situation is somewhat complicated by the fact that various types of complexes [22] that show different levels of stability in various solvents can be born, as shown by recently published data for related structures. [23] According to theoretical calculations, hydrogenbonded structures of nucleic acid bases are most stable in chloroform, T-shaped structures are preferred in dimethyl sulfoxide, and stacked structures predominate in methanol.…”
Section: Resultsmentioning
confidence: 98%
“…However, for characterizing the transition states and the reaction intermediates, the situation is somewhat complicated by the fact that various types of complexes [22] that show different levels of stability in various solvents can be born, as shown by recently published data for related structures. [23] According to theoretical calculations, hydrogenbonded structures of nucleic acid bases are most stable in chloroform, T-shaped structures are preferred in dimethyl sulfoxide, and stacked structures predominate in methanol.…”
Section: Resultsmentioning
confidence: 98%
“…The solutions for the NMR and IR experiments were obtained by dissolving the appropriate amounts of trans-RSV in DMSO-d 6 …”
Section: Methodsmentioning
confidence: 99%
“…[5] Furthermore, it is noteworthy that the interactions are widely applicable to the molecular recognition of host-guest molecules. [6,7] Aromatic antitumour antibiotics, such as doxorubicin, daunomycin, mitoxantrone, and actinomycin are widely used in clinical practice as basic components of combinations of drugs designed for treatment of various types of human cancers. It has been shown that at millimolar concentrations in aqueous solution, there is a strong tendency for aromatic anticancer drugs to exhibit self-association forming dimers and higher-order aggregates, which are stabilized by stacking interactions of the aromatic chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…In Eqn (10) 6 , represents the shift at infinite dilution (monomeric N) and 6, the shift of a molecule in an infinitely long stack, while K is the association constant as defined in Eqn (8). By ignoring species larger than dimers, a relationship analogous to Eqn (10) is obtained: 6, is replaced by cSD, the upfield shift in a dimer, and K is replaced by 2K, (i.e.…”
mentioning
confidence: 99%